Fatigue in systemic lupus erythematosus and other autoimmune skin diseases. (22nd November 2018) - Tarazi, M.; Gaffney, R.G.; Pearson, D.; Kushner, C.J.; Werth, V.P.
Summary: Background: Fatigue is a well‐established symptom in systemic lupus erythematosus (SLE), but has not been well characterized in other skin‐limited autoimmune diseases such as cutaneous lupus erythematosus (CLE), amyopathic dermatomyositis (ADM) or autoimmune blistering diseases (AIBD). Objectives: In this retrospective study, we compared fatigue in controls ( n = 84) with that in patients enrolled in prospective longitudinal databases with SLE ( n = 165), CLE ( n = 226), ADM ( n = 136) and AIBD ( n = 79). Methods: We used the 36‐Item Short Form Survey (SF‐36) vitality scale to analyse median scores and the percentages of patients with clinically significant fatigue (defined as a score ≤ 35) between experimental groups and controls. Results: Median and interquartile range (IQR) vitality scores demonstrated greater fatigue in the experimental groups (SLE 35, IQR 20–55; CLE 50, IQR 30–70; ADM 50, IQR 30–65; AIBD 55, IQR 35–70) than in controls (73, IQR 65–85) ( P < 0·05 for each experimental group vs. control). The SLE group had worse fatigue than all of the other groups ( P < 0·05 SLE vs. each group), but there was no difference between the CLE, ADM or AIBD groups (all P > 0·05). In addition, the experimental groups had more clinically significant fatigue (score ≤ 35) (SLE 44·2%, CLE 25·2%, ADM 31·6%, AIBD 24·1%) than controls (2%) ( P < 0·01 for each experimental group vs. control). The SLE group had more clinically significant fatigue than the CLE group ( P < 0·01); however, there was no difference in clinically significant fatigue between SLE and either ADM ( P = 0·17) or AIBD ( P = 0·055). Conclusions: These findings demonstrate that patients with skin‐limited autoimmune disease experience more fatigue than controls. Fatigue is an important symptom that negatively affects quality of life for patients. It should be addressed by clinicians and measured in future clinical trials. Abstract : What's already known about this topic? Fatigue is a well‐established symptom of systemic lupus erythematosus, but has not been well characterized in skin‐limited autoimmune diseases. What does this study add? This study aims to examine fatigue in patients with cutaneous lupus erythematosus, amyopathic dermatomyositis and autoimmune blistering diseases. Plain language summary available online Respond to this article